Alex and the dragon - Brian, Janeen; Buttfield, Nick (Macmillan Education Australia South Yarra [Vic.], 1999)
Alex and the Dragon by Janeen Brian is an imaginative children$1 (Bs book that follows the adventures of a young boy named Alex, who encounters a friendly dragon. Initially frightened, Alex soon discovers that the dragon is not only gentle but also possesses magical abilities. Together, they embark on a thrilling journey filled with exciting escapades and valuable lessons about courage, friendship, and the power of believing in oneself. As Alex learns to confront his fears and embrace the unknown, the story encourages young readers to explore their imaginations and understand the importance of kindness and acceptance. With captivating illustrations and a whimsical narrative, Alex and the Dragon is a delightful tale for children.s